ANALISIS DISTRIBUSI PENDAPATAN RUMAH TANGGA GAPOKTAN TUNAS BERDURI PENERIMA DANA PUAP DI DESA KUALU NANAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Wahyuni '; Eri Sayamar; Shorea Khaswarina (Indonesian Journal of Agricultural Economics, 2012)
Rural poverty is the main problem to overcome national can not be delayed andshould be a priority in the implementation of social welfare development.Government in poverty alleviation and job creation in rural areas, has launchedMandiri National Community Empowerment Program (PNPM-M). The presenceof the PNPM-Mandiri through PUAP is expected to change the societies, both interms of income and income distribution. From the results showed that therespondents' income from the agricultural sector amounted to Rp 124,387,319 or90.9% of total revenue. Revenue from non-agricultural sector amounted to Rp12.425 million or 9.1% of total income respondents, the average income permonth of Rp 5,472,493. Through analysis of the income distribution ofrespondents' income, gini index ratio of 0.35 at the farmer respondents. Thisfigure shows that there is inequality in the income of farmers was lower inresponders. This can occur because of differences in income are quite evenlyamong respondents. Based on the analysis of the level of welfare by theDirectorate of Rural Development Year 1991/1992, as many as 81% or 20 kk ofthe respondents had been in poor condition. This indicates that the purpose of theprogram is to increase the level PUAP welfare/beneficiary PUAP fund has beenreached.Keywords: PUAP, revenue, income distribution.